The impact of changes in taste, smell, and eating behavior in children with cancer undergoing chemotherapy: A qualitative study - van den Brink, Mirjam; ter Hedde, Minke M.; van den Heuvel, Emmy; Tissing, Wim J. E.; Havermans, Remco C. (Frontiers in Nutrition, 2022)
Background and aims Taste changes are the third most common bothersome symptom during treatment in children with cancer. However, it is still unclear what the essence of these taste changes are, to what degree concomitant changes in sense of smell qualify this bothersome treatment symptom and how much of an impact these changes have on the life of children with cancer. The aim of this study was to explore characteristics of both taste and smell changes and to gain insight into the impact of these changes in children with cancer receiving chemotherapy. Methods Semi-structured interviews were performed until data saturation was achieved in each age group (6–12, 13–17 years). This resulted in an in-depth description of taste and smell changes, including its impact on the life of 27 children with various cancer types receiving chemotherapy. Thematic analysis of interview data was performed. Results Interview data could be grouped into three main themes, namely changes in (1) taste, (2) smell, and (3) eating behavior. As expected, most children reported experiencing taste and smell changes just after start of treatment, but changes varied greatly between children; that is, some reported changes in intensity (increased or decreased), whereas others reported different perceptions or preferences (from sweet to savory). Taste and smell changes (regardless of direction) negatively impacted quality of life, with these changes commonly described as “disappointing” or “frustrating.” Interestingly, particular chemotherapeutic agents were frequently mentioned regarding taste and smell changes, prompting sensory-specific coping strategies. Children's eating behavior changed in terms of alterations in food liking and appetite, sometimes due to chemosensory changes, but children also mentioned specific medication or hospital food being responsible for their altered eating behavior. Conclusions Both taste and smell changes are common in children with cancer. The essence of these changes varies widely, but taste and smell changes are generally considered bothersome treatment symptoms. Ways to cope with taste or smell changes specifically were described by the children warranting further research and offering the opportunity for enhancing patient-centered care.